A physics-based algorithm to perform predictions in football leagues - Stock, Eduardo Velasco; da Silva, Roberto; Fernandes, Henrique A. (Physica A, 2022)
In this work, we extended a stochastic model for football leagues based on the team’s potential (da Silva et al., 2013) for making predictions instead of only performing a successful characterization of the statistics on the punctuation of the real leagues. Our adaptation considers the advantage of playing at home when considering the potential of the home and away teams. The algorithm predicts the tournament’s outcome by using the market value or/and the ongoing team’s performance as initial conditions in the context of Monte Carlo simulations. We present and compare our results to the worldwide known SPI predictions performed by the “FiveThirtyEight” project. The results show that the algorithm can deliver good predictions even with a few ingredients and in more complicated seasons like the 2020 editions where the matches were played without fans in the stadiums. •We propose a physics-based algorithm to perform predictions in football.•We use Monte Carlo simulations to evolute the teams’ potentials.•Our adaptation considers the advantage of playing at home.